Automatic pre‐treatment and multiblock analysis of flavor release and sensory temporal data simultaneously collected in vivo - Peltier, Caroline; Visalli, Michel; Labouré, Hélène; Hélard, Cantin; Andriot, Isabelle; Cordelle, Sylvie; Le Quéré, Jean-Luc; Schlich, Pascal (Journal of chemometrics, 2024)
Proton Transfer Reaction-Time-of-Flight- Mass Spectrometry (PTR-ToF-MS) is an analytical chemistry technique that can be used for measuring the concentration of volatile organic compounds directly in the subjects’ noses (nosespace, in vivo analysis) during a tasting and over time. It can be combined with temporal sensory methods such as Temporal Dominance of Sensations (TDS) or Temporal Check All That Apply (TCATA) in order to obtain simultaneous sensory and physico-chemical signals. This paper aims to provide a methodology to analyze in vivo PTR-MS and temporal sensory data and illustrate it on a real dataset. First, relevant pretreatments of PTR-MS data were established, including breathing correction, blank periods removal and standardization. Then, a statistical multiblock analysis was presented: the Regularized Generalized Canonical Correlation Analysis (RGCCA). The versality of the approach was demonstrated, as it can be used to answer most of problematics (exploratory or supervised). Finally, this methodology is illustrated on a dataset of PTR-MS and TDS or TCATA data collected simultaneously. In this study, 16 semi-trained subjects evaluated 3 chocolates in TDS and TCATA on six flavor attributes (Spicy, Cocoa, Woody, Fruity, Roasty and Dry Fruits) with 2 replicates for each sensory method. Results showed that TCATA and TDS gave similar results, but TDS was shown to slightly better preserve the PTR-MS observed product configuration than TCATA. All computing tools developed in this work are freely available.